The Impact of Subcultural Differences on Language use in the Algerian Society - Belabassi, Fatima (My University, 2017)
This work is devoted to understand the extent to which culture and language are interrelated and the possibility of language to be affected by culture. We have tackled the different aspects of language besides the various contributions of Noam Chomsky to understand Language and how could it be acquired or learned; moreover, we highlighted interculturality and its basics. Mainly, our focus was on the different linguistics backgrounds between two distinct but interrelated cultures; Algerian Arabic and Tamazight and the importance of raising awareness among them to communicate freely. In this vein, as far as the practical part is concerned, we opted for a questionnaire as a research tool to answer our research questions. We deduced from this work that culture and language are tightly linked and if culture is a set of behaviors, traditions, and customs; language is but a tool to transmit culture from one generation to another and from one region to another. Being interculturally competent is very important, to get rid of miscomprehension and egocentrism.
Case of study Arabs from Mostaganem Tiaret and Relizan and Amazigh from Tizi Ouzou Bejiaa and Bouira
Keywords: Language; Culture; Interculturality